Social Resilience Assessment in Reducing Potential Risk of Earthquake in Surabaya - Myrna Augusta Aditya Dewi; Mohammad Arif Rohman; Eko Budi Santoso (Institut Teknologi Sepuluh Nopember, 2020)
Surabaya has a potential risk of earthquakes, refer to the 2017 Indonesian Earthquake Source and Hazard Map issued by the National Center for Earthquake Studies (Pusat Gempa Nasional-PUSGEN). Surabaya city readiness in responding this issue is indicated by the community resilience. Therefore, it is important to assess the social resilience to find out the current capacity of communities in responding to earthquake risk. The research targeted the area around the Surabaya Fault with potentially high seismic hazard, consisting of 8 districts and 23 sub- districts. 22 variables were obtained by doing a literature review and expert judgment, that are 11 variables for social vulnerability and 11 variables for preparedness. We collect the data by distributing questionnaires to 116 respondents, the head of neighbourhood units, selected by simple random sampling. We analyze the data using Confirmatory Factor Analysis (CFA), descriptive statistics and Geographic Information Systems (GIS)-based mapping. Based on CFA, there are 7 valid variables of social vulnerability and 10 variables of preparedness for index assessment. The social vulnerability assessment has an index value of 2.27, while preparedness has an index value of 1.99. The index value shows that both of these indicators are in the low-to-medium category. Then, the social resilience index is assessed as the ratio of preparedness and social vulnerability index. By comparing these two indicators, Surabaya has an index value of 0.88 for social resilience or categorized as less resilient in responding to the earthquake risk.